Histopathology associated with angiostrongylosis in akodon species (Rodentia: Sigmodontinae) from sierra de la ventana, buenos aires, Argentina - Robles, Maria del Rosario (2012)
Angiostrongylus is a metastrongylid nematode genus that includes species found in carnivores, rodents, and occasionally primates (including humans). About 100 species of wild sigmodontine rodents occur in Argentina, 16 of which are species of Akodon. The lungs of Akodon azarae and Akodon dolores from Sierra de la Ventana, Buenos Aires, Argentina, were examined, and 2 of 10 A. dolores specimens were positive for angiostrongylosis, showing macroscopic lesions of verminous pneumonia. Adults found were identified as Angiostrongylus morerai. Histopathology of the lungs revealed multiple nodules in the interstitium, alveoli, and vessels, resulting in interstitial fibrosis and the destruction of small capillaries and arterioles. Since extensive pathology in the lung was noted here from only 2 adults, it is probable that heavier infections may cause mortality in their hosts. This is the first record of this nematode species from A. dolores, expanding its geographic distribution to the southwest of Buenos Aires Province, and the first description of the histopathology of larval angiostrongylosis in a wild rodent from South America. © American Society of Parasitologists 2012.